(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The activity of the public administration bodies seeks the effective fulfillment of the objectives and goals set in the regulations, plans and management commitments, under the guidance of the policies and strategies established by public officials invested, by law, with the competence to implement them. Today, the way in which these objectives are met has changed radically, and public management is forced to innovate and implement new strategies to create value and respond to the demands of citizens. Innovation is the product of a combination of factors that include the use of Information and Communication Technologies, but emphasizing the correct way to use them, integrating them into the mission and vision of the public institution. The value of the public is a novel concept for measuring the achievement of objectives that currently emphasizes the accountability of the resources used. A look at these two components of public management is the fundamental purpose of this essay.